2016
DOI: 10.1098/rstb.2015.0376
|View full text |Cite
|
Sign up to set email alerts
|

The role of the basolateral amygdala in the perception of faces in natural contexts

Abstract: One contribution of 15 to a theme issue 'Attending to and neglecting people'. The amygdala is a complex structure that plays its role in perception and threatrelated behaviour by activity of its specific nuclei and their separate networks. In the present functional magnetic resonance imaging study, we investigated the role of the basolateral amygdala in face and context processing. Five individuals with focal basolateral amygdala damage and 12 matched controls viewed fearful or neutral faces in a threatening o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 89 publications
1
20
0
Order By: Relevance
“…BLA connections to primary visual cortex are reported in primates 61,62 although, to our knowledge, not in mice. The relevance of these connections are apparent in the context of primate 63,64 and human 65 studies showing BLA involvement in the processing of facial expressions; however, they may also be relevant in rodents.…”
Section: Blaam Neurons and Visual And Spatial Informationmentioning
confidence: 98%
“…BLA connections to primary visual cortex are reported in primates 61,62 although, to our knowledge, not in mice. The relevance of these connections are apparent in the context of primate 63,64 and human 65 studies showing BLA involvement in the processing of facial expressions; however, they may also be relevant in rodents.…”
Section: Blaam Neurons and Visual And Spatial Informationmentioning
confidence: 98%
“…In humans, the amygdala as a whole is thought to play a key role in emotional and social cognitive processes (e.g. Adolphs et al, 2005, Kliemann et al 2012, Hortensius et al, 2016), and accordingly, its dysfunction is implicated in psychopathologies, such as mood disorders (Phillips et al, 2003; Siegle et al, 2002), anxiety disorders (Birbaumer et al, 1998; Rauch et al, 2003), and developmental disorders (Baron-Cohen et al, 2000; Dziobek et al, 2010). Additionally, several post mortem studies have shown that the amygdala is a common site for neurofibrillary tangles and senile plaques in mild cognitive impairment (Merkesbery, 2010) and Alzheimer’s disease (Yilmazer-Hanke, 1998) as well as Lewy bodies (Kotzbauer et al, 2011, Fujishiro et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Application of this technique is relatively easy and does not require considerable load of effort or time. Thus, it has been extensively used in research on the role of the amygdala subregions in facial emotion perception (Hurlemann et al 2008, Barbour et al 2010, Hortensius et al 2016, auditory stimulation with pleasant and unpleasant music excerpts (Ball et al 2007) and emotional voices (Frühholz and Grandjean 2013) or perceiving social cues (Freeman et al 2014). However, as critically pointed by Prévost and colleagues (2011), the probabilistic maps might not be applicable for the studies with younger sample than the one used in the study by Amunts and colleagues due to extensive age-related changes in structure of the brain.…”
Section: Parcellation Of the Amygdalamentioning
confidence: 99%